Supporting language in schools: Evaluating an intervention for children with delayed language in the early school years. (June 2016) - Lee, Wendy; Pring, Tim
Extensive evidence exists that many children who experience early socio-economic disadvantage have delayed language development. These delays have been shown to exist when children start school and appear to persist through their education. Interventions that can help these children are desirable to ease the difficulties they have in school and to address the loss in human capital which these children represent. We evaluated an intervention (Talk Boost) to treat children's receptive and expressive language in the early school years. A between-schools design was used. Eighteen schools in socially deprived areas were randomly assigned to receive the intervention or to act as waiting controls. Children in reception classes and in Years 1 and 2 attended language groups. The evaluation used the standard procedure for the intervention. Teachers were given guidance on selecting appropriate children, and the intervention was carried out by teaching assistants; 180 children participated. Those with English as their first language and those learning it as an additional language increased their scores significantly more than did controls. Most of the children selected had significant delays, which did not diminish as they advanced in school. Despite their improvement the treated children remained behind the expected level for their age after the intervention. These findings add to previous evidence that intervention can help children who start school with delayed language. There appears to be insufficient awareness of the communication needs of these children and of their likely inability to access other areas of the curriculum as a result.